World of insects - Adam, Nur Azura (Universiti Putra Malaysia Press, 2013)
Earth is greatest living puzzle in the world which is a collection of worlds within world. One of the most intriguing and mysterious of all is the world of insects. Insects dominate by over 80% of all living creatures on our planet. They can be found almost in every possible environment from aerial spaces, on land and the aquatic environment.